An analysis on genre and lexical density of 10 reading texts in the grade 10th experimental English textbook in Vietnam - Đinh, Tan Tho (2019)
References: p.55 - 58; Master thesis of Thu Dau Mot University. Major: English language; Code: 8220201; 5 chapters: Introduction; literature review; research methodology; findings and discussion; conclusion and implications; Đồng ý về việc phục vụ đọc trực tuyến, không ý kiến về việc chép file, cho photo 50% tài liệu